2013
DOI: 10.1161/hypertensionaha.113.01965
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Risk of Hypertension

Abstract: Abstract-Published literature reports controversial results about the association of physical activity (PA) with risk of hypertension. A meta-analysis of prospective cohort studies was performed to investigate the effect of PA on hypertension risk. PubMed and Embase databases were searched to identify all related prospective cohort studies. The Q test and I 2 statistic were used to examine between-study heterogeneity. Fixed or random effects models were selected based on study heterogeneity. A funnel plot and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
8
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(139 citation statements)
references
References 42 publications
8
118
8
5
Order By: Relevance
“…Contrary to these findings, the effect of self-management on medical risk factors was not significant. The efficacy of lifestyle modification at improving blood pressure [46][47]and glucose control [48], as well as lowering cholesterol [49] is well established. A path in which lifestyle behaviour modification precedes changes to medical conditions is thus implied and represents a plausible explanation as to why a significant effect was observed on lifestyle behaviour but not medical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these findings, the effect of self-management on medical risk factors was not significant. The efficacy of lifestyle modification at improving blood pressure [46][47]and glucose control [48], as well as lowering cholesterol [49] is well established. A path in which lifestyle behaviour modification precedes changes to medical conditions is thus implied and represents a plausible explanation as to why a significant effect was observed on lifestyle behaviour but not medical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian ini juga sesuai sebuah metaanalisis yang menunjukkan tidak ada hubungan antara aktivitas fi sik dengan kejadian hipertensi (12). Sebaliknya, penelitian di Yogyakarta menunjukkan terdapat hubungan yang signifi kan antara aktivitas fisik dan hipertensi pada lansia di Kecamatan Kasihan Bantul (p=0,004) (13).…”
Section: Hubungan Aktivitas Fisik Dengan Kejadian Hipertensiunclassified
“…Physical activity positively affects health status in different types of populations (1)(2)(3)(4)(5)(6)(7)(8)(9). Previous studies in patients with CKD and patients on maintenance hemodialysis (MHD) have shown associations of physical activity with improved outcomes (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%